FALSIFIKASI SEBAGAI DASAR EPISTEMOLOGI KARL RAYMUND POPPER DALAM MELIHAT PROBLEM ILMU PENGETAHUAN - Purwosasaputro, Supriyono (FPIPSKR Universitas PGRI Semarang, 2023)
The problem of science in the Western tradition is often determined by the demarcation of truth it constructs. Thus, many figures claim that their method is the final method. This was also called for Popper to depart from his methodology that doubted the accuracy of the inductive-verification method and replaced it with a deductive-falsification method with a trial and error method. Here it appears that Popper has paid little attention to the prevalence of (normal-research) scientists who have factually been shown to enable the growth of new scientific knowledge based on everyday sources of knowledge (as stated by Thomas S. Kuhn and Imre Lakatos). This research is qualitative library research using analytical methods. The result of this study was a critique of Raymund Popper's falsification theory of the correctness of the propositions of science